War veterans and fascism in interwar Europe - Alcalde, Ángel (Studies in the social and cultural history of modern warfare, 2017)
"This book analyses the transnational relationship between war veterans and fascism in interwar Europe. For decades, historians have strived to explain why the European continent, only twenty years after a cataclysmic war of unprecedented murderous dimensions, became involved in a new, even more horrendous, world conflict. Although there were important democratic experiences and remarkable advances in many facets of human life, the interwar period saw the progressive demolition of the peaceful order for which many people had hoped in the wake of the Great War. While at the beginning of 1919 democracies clearly dominated Europe, by June 1940 they were the exception to the rule. This eclipse of democracy, marked by violent conflicts and civil wars, cannot be understood without placing fascism at its centre. Fascism was a product of the First World War experience, and fascism can also be considered to have triggered the Second World War. In this scenario, explaining the links between fascism and war veterans, the men who were also a direct legacy of the Great War, remains crucial"--Introduction